Book of blues - Kerouac, Jack 1922-1969 (Penguin poets, 1995)
Although he is best known as a writer of prose, Jack Kerouac was an important poet, his work described by Michael McClure as "startling in its majesty and comedy and gentleness and vision". These eight extended poems, composed between 1954 and 1961, offer exuberant forays into language and consciousness that combine rich imagery, complex internal rhythms, and a reverent attentiveness to the moments.